KEMAMPUAN KINERJA KEUANGAN MEMODERASI PENGARUH CSR DAN STRUKTUR MODAL PADA NILAI PERUSAHAAAN MANUFAKTUR - sri wahyuni, kadek nonik; Badera, Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.09.TAHUN 2016, 2016)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 ABSTRACT This study aims to determine the influence of Corporate Social Responsibility (CSR) and the Capital Structure on Firm Values Manufacturing Company classified as High and Low Profile with financial as moderating variables. This research, with total population of 132 companies in Indonesia Stock Exchange, using non-probability sampling method, using purposive sampling technique in order to obtain the 10 companies for sample. The analysis showed that the Corporate Social Responsibility effect on the value of the company, while the capital structure does not affect the firm value of the company. The analysis also shows that financial performance is proxied by the ROA was not able to moderate the influence of Corporate Social Responsility and capital structure on the firm value of companies classified as High and Low Profile. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Corporate Social Responsibility, Capital Structure, Financial Perfomance, and Firm Value